A Review of Cellulose and Cellulose Blends for Preparation of Bio-derived and Conventional Membranes, Nanostructured Thin Films, and Composites. (2nd January 2018) - Douglass, Eugene F.; Avci, Huseyin; Boy, Ramiz; Rojas, Orlando J.; Kotek, Richard
ABSTRACT: Cellulose has been used as a raw material for the manufacture of membranes and fibers for many years. This review gives the background of the most recent methods of treating or dissolving cellulose, and its derivatives to form polymer films or membranes for a variety of applications. Indeed, some potential applications of bacterial cellulose, nanofibrillar cellulose (NFC) for films showing enhanced barrier characteristics are reviewed as well as the utilization of cellulose nanonocrystals (CNC) for production of highly oriented super strong films or thin films is discussed. Because of the success of the Lyocell process as well as the amine/metal thiocyanate solvent blends of cellulose and other polysaccharides like starch, chitosan, and other natural polymers. Consequently, the use of cellulose (or its derivatives) and another polysaccharide dissolved as a blend is also elaborated. It is our hope that the reader will want to follow up and investigate these new systems and use them to develop end use materials for all sorts of applications, from medical to water filtration, or electrogels for use in batteries.